Perception of Time Value of Money and Economic Value of Time among Sharia Bank Customers - Fadhiya, Kamila; Indra Cahya Kusuma; Didi (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to examine the influence of perceptions of understanding the concept of time value of money and economic value of time on the Islamic financial system, with religious commitment as a mediating variable. The study also examines the differences in perception between customers who only use Islamic banks and Islamic customers who also use conventional banks in Bogor Regency. A total of 100 respondents from Islamic bank customers in Bogor Regency were selected as samples using purposive sampling techniques. The data were analyzed using the SEM-PLS method with the help of SmartPLS 3.0, as well as a comparative independent sample t-test with IBM SPSS 26. The results of the study indicate that perceptions of the time value of money and the economic value of time have an effect on the Islamic financial system. Religious commitment is able to mediate these influences. The difference test showed no significant difference between customers who only use Islamic banks and customers who also use conventional banks. This shows that public understanding of the concept of Islamic finance is still minimal.